2023
DOI: 10.3847/psj/ace7d0
|View full text |Cite
|
Sign up to set email alerts
|

Col-OSSOS: Evidence for a Compositional Gradient Inherited from the Protoplanetary Disk?

Michaël Marsset,
Wesley C. Fraser,
Megan E. Schwamb
et al.

Abstract: In the present-day Kuiper Belt, the number of compositional classes and the orbital distributions of these classes hold important cosmogonic implications for the solar system. The Colours of the Outer Solar System Origins Survey (Col-OSSOS) recently showed that the observed color distribution of small (H ⪆ 6) trans-Neptunian objects (TNOs) can be accounted for by the existence of only two composition classes, named BrightIR and FaintIR, where the range of colors in each class can be modeled as mixtures of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…They propose that the three groups provide a picture of the ice retention lines in the Solar System that likely occurred in the outer protoplanetary disk, just before a major planetary migration. Recent results strengthen NPA23 hypothesis (Nesvorný et al 2020;Pirani et al 2021;Marsset et al 2023).…”
Section: Introductionsupporting
confidence: 74%
“…They propose that the three groups provide a picture of the ice retention lines in the Solar System that likely occurred in the outer protoplanetary disk, just before a major planetary migration. Recent results strengthen NPA23 hypothesis (Nesvorný et al 2020;Pirani et al 2021;Marsset et al 2023).…”
Section: Introductionsupporting
confidence: 74%
“…As in Figure1, the semimajor axis is scaled by three different amounts, as indicated in the x-axis and separated by gaps, and the symbol shapes are preserved, but the colors of the points indicate BrightIR classification (black) and FaintIR classification (red). The low-inclination and low-eccentricity 4:3 resonator at 36.4 au is particularly evident, as is the classification-inclination dependence, particularly at large-a, noted byMarsset et al (2019) andMarsset et al (2023). Neptune is indicated by the large blue circle.…”
mentioning
confidence: 84%
“…The distribution of red and very red TNO surfaces has been reported to have a correlation between inclination (for a recent analysis, see Marsset et al 2019) and eccentricity (Ali-Dib et al 2021) to surface color, which is inferred to be related to differences of formation location and the effects of planetary migration on the populations. The correlation between inclination and surface classification holds when the FaintIR/BrightIR classification system is used (Marsset et al 2023). Marsset et al (2019) also identified a dependence between the final inclinations of TNOs and their formation distances.…”
Section: Introductionmentioning
confidence: 92%